Un théâtre astral et « révolutionnaire » : les visions « fanta-scientifiques » de Paul Scheerbart - Cristina Grazioli (ReS Futurae, 2021)
Paul Scheerbart (1863-1915) is a well-known author in studies on the origins of science fiction in Germany and is often quoted for his contribution to the aesthetics of modernist architecture. Yet he was rarely studied for his theatrical conceptions and writings; his theatrical work was never considered enough, nor under the prism of the anticipations of SF theatre. The author's revolutionary conception is approached here by relating his theatrical project to his utopian thought, which unfolds in the fantastic inventions of an essential stage and at the same time a phantasmagorical set thanks to the lighting effects of the 'astral' presences. We propose here the perspective of a continuity between the stage as a place of realisation of utopia, and the transparency of light as a dimension that aims at opening up to other worlds; theatre as a condition that fuses the dimension of the present (of presence) is investigated, within the deployment of the futuristic imaginary of science fiction. An important element of our approach to this visionary author, who anticipated many conceptions and practices of contemporary art and stage, is the knowledge of the world of technology and inventions, which Scheerbart transfigures in his innovative 'astral' theatre.